PERBEDAAN HASIL BELAJAR PESERTA DIDIK YANG MENGGUNAKAN MODEL PEMBELAJARAN ACTIVE LEARNING TIPE COURSE REVIEW HORAY DENGAN TIPE THINK PAIR SHARE - Yayat Hidayat (Jurnal Pendidikan Teknologi Informatika dan Sains, 2020)
This research is motivated by the fact that in Class VIII SMP Plus Ma'arif NU Pangandaran that Learning is still teacher centered, lack of student involvement during the learning process, students generally act passively and are afraid or embarrassed to ask questions when experiencing difficulties in learning, not optimal use of the active method learning type course review horay, and not yet optimal use of active learning methods think pairs share type. The purpose of this study was to study, find out, and analyze: (1) Improvement of student learning outcomes (Pretest and Posttest) using the active learning model type course review horay in Islamic Religious Education Class VIII Middle School Plus Ma'arif NU Pangandaran. (2) Improving student learning outcomes (Pretest and Posttest) by using active learning learning models think pair share type in Islamic Religious Education Subjects Class VIII SMP Plus Ma'arif NU Pangandaran. (3) Differences in student learning outcomes by using the active learning model review course type horay with the type of think pair share in Islamic Religious Education Subjects Class VIII SMP Plus Ma'arif NU Pangandaran. The research method used is experiment. "Experimental research can be interpreted as a research method used to look for the effect of certain treatments on other variables under tightly controlled conditions. The results showed that (1) Students had increased knowledge after applying an active learning type course review horay model with an average posttest score of 77.39 and a pretest value of 66.9 with an N-Gain value of 0.33 based on the table . 3.16. in the medium category. (2) Students have experienced an increase in knowledge after applying the active learning learning model think pair share with an average posttest score of 65.65 and a pretest value of 76.09 with an N-Gain value of 0.33 based on the table. 3.16. in the medium category. (3) The test results are known that the value of t arithmetic is greater than t table (2.054> 1.721), meaning that there are differences in student learning outcomes using active learning models type course review horay with the type of think pair share in Islamic Religious Education Subjects Describe Consuming Halal Food and Beverages and Stay Away from the Unlawful Class VIII of SMP Plus Ma'arif NU Pangandaran, because of their significant influence.